(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article examines how sports aerobics training sessions can be structured and applied to develop the physical qualities of female university students in a sports-university context. The study proceeds from the idea that sports aerobics, as a coordinated combination of rhythmic motor actions, strength elements, flexibility demands, and continuous movement patterns, creates a training environment capable of simultaneously stimulating several fitness components. The research problem is formulated around the need to identify methodically grounded training content that improves key physical qualities relevant to young women’s health, athletic readiness, and sustainable participation in physical activity. The article conceptualizes physical qualities as an integrated set that includes strength (particularly muscular endurance and strength endurance), speed-strength abilities, general and special endurance, flexibility, coordination, balance, and agility. Within this framework, sports aerobics sessions are treated not as generic “fitness classes,” but as a pedagogically managed training system in which intensity, complexity, movement repertoire, and recovery are controlled to achieve measurable adaptations.